Conflict-sensitive adaptation governance: Assessing Kenya’s County Climate Change Fund - Medina, Leonardo; Schapendonk, Frans; Jaskolski, Martina; Osumba, Joab; Jebiwott, Alice; Singh, Radhika; Takaindisa, Joyce; Pacillo, Grazia (2025)
The Conflict Sensitive Adaptation Governance analysis aims to evaluate multi-level climate adaptation policies on whether these instruments are intentionally designed, implemented, and assessed for their ability to prevent new conflicts, create legitimate venues for conflict resolution, and harness their peacebuilding potential. This analysis focuses on Kenya’s County Climate Change Fund (CCCF) mechanism. This adaptation policy instrument operates under the principles of locally-led adaptation. It is intended to assist county governments across Kenya in establishing a dedicated fund that can be readily accessed by community-led adaptation committees to finance locally prioritized and designed adaptation projects. This research developed a practical framework for evaluating climate adaptation policies through a conflict sensitivity lens. The framework includes 22 assessment criteria to guide the analysis across three policy phases. the framework is organized around three key dimensions which can theoretically enable governance conditions for conflict sensitivity to emerge: multilevel governance, adaptive governance, and representative governance. The County Climate Change Fund (CCCF) provides a promising model for conflict-sensitive climate governance by empowering ward-level planning committees and fostering inclusive, community-driven decision-making. Despite its successes, several opportunities for conflict sensitivity and peacebuilding integration remain. This report outlines key findings and recommendations.